Observation of five new narrow Ω0c states decaying to Ξ+cK−. - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Jurik, N; et al. (American Physical Society, 2017)
The Ξ+cK− mass spectrum is studied with a sample of pp collision data corresponding to an integrated luminosity of 3.3  fb^-1, collected by the LHCb experiment. The Ξ+cK− is reconstructed in the decay mode pK-π+. Five new, narrow excited Ω0c states are observed: the Ωc(3000)^0, Ωc(3050)^0, Ωc(3066)^0, Ωc(3090)^0, and Ωc(3119)^0. Measurements of their masses and widths are reported.